Daratumumab, bortezomib, cyclophosphamide and dexamethasone in newly diagnosed and relapsed multiple myeloma: LYRA study. (3rd March 2019) - Yimer, Habte; Melear, Jason; Faber, Edward; Bensinger, William I.; Burke, John M.; Narang, Mohit; Stevens, Don; Gunawardena, Sriya; Lutska, Yana; Qi, Keqin; Ukropec, Jon; Qi, Ming; et al.
Summary: This United States community study evaluated the combination of daratumumab, bortezomib, cyclophosphamide and dexamethasone (D‐VCd) in newly diagnosed multiple myeloma (NDMM) and relapsed multiple myeloma (RMM). Patients received 4–8 induction cycles of bortezomib 1·5 mg/m 2, cyclophosphamide 300 mg/m 2 and dexamethasone 40 mg weekly. Intravenous daratumumab 16 mg/kg was administered as approved except for a split‐first dose in Cycle 1. Eligible patients underwent autologous stem cell transplantation. All patients received ≤12 daratumumab maintenance doses monthly. Eighty‐six NDMM and 14 RMM patients received ≥1 treatment dose. In NDMM patients, very good partial response or better (≥VGPR) and overall response rates after 4 induction cycles were 44% (primary endpoint) and 79%, respectively, and 56% and 81% at end of induction. The 12‐month progression‐free survival (PFS) rate was 87%. Efficacy was also observed in RMM patients. Fatigue (59%) and neutropenia (13%) were the most frequent treatment‐emergent adverse event (TEAE) and grade 3/4 TEAE, respectively. Infusion reactions occurred in 54% of patients, primarily during the first dose, and were mild (2% grade 3). The first 2 daratumumab infusions were 4·5 and 3·8 h (median). Overall, D‐VCd was well tolerated, split‐first daratumumab dosing was feasible, the ≥VGPR rate after 4 cycles was 44% and the 1‐year PFS rate was 87%.